PENINGKATAN ILMU KEOLAHRAGAAN GURU SMP DI KABUPATEN NGANJUK MELALUI PEMBERIAN MATERI KONSEP DBON - Setijono, Hari; Ashadi, Kunjung; Wibowo, Sapto; Wiriawan, Oce; Muhammad, Heryanto Nur (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The lack of understanding by sports teachers in Nganjuk Regency regarding the importance of implementing the DBON concept in improving physical quality means that sports achievements in Nganjuk Regency cannot be maximized. This condition occurs due to the government's lack of attention to improving human resources, or in this case teachers, regarding the development of sports science and various existing physical activities to be applied to learning in schools, so that they can improve the quality of students. This socialization was attended by 20 junior high school teachers in Nganjuk Regency. The method used in this activity is to convey material about the DBON concept and various physical activities orally. The materials used in this activity were DBON Concept powerpoint materials as well as providing photocopies of the materials and e-book files "Easy Ways to Practice Gym Ball and Be Diligent in Sports" to participants so they could study independently. After participating in this activity, the participants stated that they experienced increased knowledge and understanding of the DBON concept as well as physical activities that they could apply at school later. The participants also hope that this kind of activity can continue to be carried out in the future